KEADAAN JALAN DI DAERAH HUTAN NON-JATI JAWA TENGAH DAN POTENSINYA DALAM AKSELERASI EROSI TANAH - Djaban Tinambunan (Jurnal Penelitian Hasil Hutan, 1993)
An investigation on forest     road  conditions  in  non-teak forests    of Kedu  Utara and kedu selatan  Forest  Districts and their soil erosion  potentials   was conducted in early  1992.  The samples  of roads investigated  were  6 segments  in kedu   Utara and other 6 segments in Kedu selatan  in Kedu  Selatan,  each of 50 m long, Forest areas distribution and road inventory  were also investigated  and collected.     It is found  that forest  sections  in both forest  districts  are spread in  several regencies    and each section  consisted  of several relative small areas   scattered in many   locations  which are seperated by villages and other  land uses. This condition becomes the constraint in practicing good forest management in the area. The total  area  used for    rood  infrastructure (combined    graveled forest roads and public  roads)  in  Kedu utara and kedu selatan are 8.30 ha (0.03%) and 60.62 ha (0.14%) respectively.   This means that an average  land lost due to roading is only 0.08%.All factors in the universal soil loss equation (USLE) for the non- teak forest areas of kedu utara and kedu selatan are in the level of high scores in terms of soil erosion acceleration potential. It is noticed in the field that many segments of forest roads have been seriously eroded, especially along the berms and ditches, and on the fill and cut sections. Better planning and construction practices of forest roads are necessary to avoid forest land damage due to soil erosion.